Language and national identity in Greece, 1766-1976 - Mackridge, Peter (Oxford : Oxford University Press, 2010)
This is a history of the great language controversy that has occupied and empassioned Greeks - sometimes with fatal results - for over 200 years. Mackridge explores the political, social and linguistic causes and effects of the controversy in its many and passionate manifestations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Greek language, Modern -- Political aspects -- History; Nationalism -- Greece -- History; Language policy -- Greece